Effectiveness Of Stone Columns As Countermeasure For Liquefiable Sandy Soil Stratum With Silt Intralayers - Simatupang, Roland Martin; Chen, Huei- Tsyr; Lee, Chung- Jung (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2015)
Numerical simulation was used to investigate effectiveness of stone column as countermeasure for liquefiable sandy soil stratum with silt intralayers. One finite element model of sand and two models for silt cases were subjected to two different stone column areas. The use of stone columns can delay and reduce the accumulation of excessive pore water pressure; although in some cases liquefaction still cannot be avoided. Stone column increases the stiffness of the sand area and able to reduces the ground settlement; however this benefit decreases as the more silt intralayers exist in the stratum.